Effect of High Speed Machining on Surface Roughness Characteristics Ra, Rq, RZ - Khare Sanchit Kumar; Gulati Piyush; Singh Jaiinder Preet; Phull G.S. (E3S Web of Conferences, 2023)
Today’s machining industries experience a variety of challenges, but achieving high quality in terms of dimensional accuracy, surface quality, and production rate is their key concern. An effort has been made in the current study to investigate the impact of HSM process parameters on different Surface Roughness characteristics Ra, Rq, and Rz. The trials were conducted on Ti-6Al-4V, a material that finds extensive use in the automotive, aerospace, and biomedical industries. Depth of cut, feed rate, cutting speed, and step over were taken into account as HSM inputs for the experiment. Similar to this, the output characteristics Surface roughness parameters Ra, Rq, and Rz were used. The trials were carried out using Taguchi’s standard L9 Orthogonal Array, and the optimization of multi responses was carried out using Grey analysis. The most significant influences on the parameters of surface roughness were found to be cutting speed and depth of cut. A confirmation experiment was performed using the ideal set of parameters to validate the study, and the results were found to be in good agreement with those of the experiment. According to the findings, the HSM method produced a superior surface quality.